An efficient 3D non-hydrostatic model for predicting nonlinear wave interactions with fixed floating structures. (15th March 2022) - Ai, Congfang; Ma, Yuxiang; Yuan, Changfu; Xie, Zhihua; Dong, Guohai; Stoesser, Thorsten
Abstract: This paper presents a three-dimensional (3D) non-hydrostatic model for the prediction of the interaction between nonlinear waves and fixed floating structures. The model solves the incompressible Euler equation by use of a semi-implicit, fractional step algorithm. The water surface elevation is treated as a single-valued function of horizontal position. In order to deal with floating structures, a new numerical algorithm is proposed which combines the immersed boundary method and the global continuity equation in the pressurized region (flow region under the structure). This new algorithm holds the symmetry of the Poisson equation and therefore results in an efficient model. The developed model is validated with the data of two test cases involving 3D nonlinear wave interactions with a floating structure. The model results are compared with experimental data or results of other models. The proposed model exhibits generally good agreement with experimental data and/or other model results, demonstrating its accuracy in resolving 3D nonlinear wave interaction with floating structures. Highlights: An efficient 3D numerical model for wave interacting with floating structures are developed. Algorithm combining the IB method and the global continuity equation is proposed. Comparisons between the present model and other model results are presented. The developed model can effectively resolve 3D wave interactions with floating structures.